Des antiquités égyptiennes au musée. Modèles, appropriations et constitution du champ de l’égyptologie dans la première moitié du xixe siècle, à travers l’exemple croisé du Louvre et du British Museum - Juliette Tanré-Szewczyk (Les Cahiers de l'École du Louvre)
This article focusses on the museum displays of Egyptian antiquities both in France and in the United Kingdom; the subject is addressed from the perspective of appropriation processes of models. This study begins with the 1808 opening of the Townley Gallery, first museum rooms fully-devoted to Ancient Egypt, in the British Museum, and ends with Samuel Birch, curator in charge of Egyptian antiquities in the BM from 1836 to 1885. It aims to compare the British’s and Louvre’s displays and to point out changes and new trends in the way Egyptian collections were regarded by the public and studied by the scholars. This study highlights that English and British models were scarcely likely to influence each other in the first half of the nineteenth-century; what Jean-François Champollion sets out for the Louvre seems to have been a singular experience which was not followed by obvious cases of appropriation.